Implementation of the Musharakah Mutanaqisah Agreement in Sharia Housing Financing - Anshara, Jessenia Hayfa (TAWAZUN: Journal of Sharia Economic Law, 2026)
The Musharakah Mutanaqisah (MMQ) contract is one of the alternative sharia housing financing that is conceptually designed to reflect the principles of partnership, joint ownership, and proportionate risk sharing between Islamic banks and customers. However, the implementation of the MMQ contract in Islamic banking practices in Indonesia still raises various legal and sharia issues. This study aims to analyze the legal position of the Musharakah Mutanaqisah contract in sharia housing financing, examine its suitability with the principles of muamalah fiqh and positive law, and assess its implementation from the perspective of maqāṣid al-syarī'ah. The research method used is normative juridical research with legislative, conceptual, and analytical approaches. Data were obtained through literature studies on Islamic banking regulations, fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), and relevant scientific literature. The results of the study show that normatively the Musharakah Mutanaqisah contract has strong legal legitimacy both according to Islamic law and positive law. However, in the practice of sharia housing financing, substantive discrepancies are still found, especially related to risk sharing, rent determination (ujrah), and the use of standard agreements that have the potential to weaken the legal position of customers. From the perspective of maqāṣid al-syarī'ah, the implementation of MMQ that is too oriented towards the certainty of bank profits risks obscuring the value of partnership, justice, and benefits. Therefore, it is necessary to strengthen sharia supervision and improve regulations so that the implementation of the Musharakah Mutanaqisah contract better reflects the principles of justice and the purpose of sharia housing financing.